Study the Relationship of Earthquake and Ionosphere Using IRI TEC for Education - Nawaphon Phansori; Sirinil Phukrongta; Onuma Kriamthaisong; Prasert Kenpankho (ASEAN Journal of Science and Engineering Education, 2022)
This research is aimed to study and analyze the relationship between the earthquake events and the disturbance of ionosphere. The method is by using the International Reference Ionosphere (IRI) model to get Total Electron Content (TEC) values and then find the correlation on earthquake events and ionosphere. The result is to be correlated at 0.056, which shows the evidence of correlationon earthquake events and ionosphere. For the future work, we  will  study  the  significant  on  the  development of earthquake  warning  system. This  study  can  be  used  for educational purposes.